Analysis of E-Service Quality on Customer Satisfaction Impact on Banking Image - Hadiyan Nur Sofyan; Nunung Ayu Sofiati; Mochammad Mukti Ali; Dadan Abdul Azis; Gurawan Dayon; Riyadi Nur Sumawidjaya; Ade Salman Alfarisi; Anggono Raras Tirto Sakti (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to analyze the influence of E-Service Quality on customer satisfaction and its impact on banking image. The research methods used are descriptive and verification methods. The descriptive method is used to describe the condition of E-Service Quality, customer satisfaction, and banking image at the time of the study, while the verification method is used to test the relationship and influence between the variables studied. E-Service Quality is measured through the dimensions of efficiency, responsiveness, compensation, and contact, while customer satisfaction is measured based on expectation and perception. The population in this study were 487 customers using electronic banking services. The sampling technique used simple random sampling, so that each member of the population has an equal opportunity to be selected as a respondent. The results show that banking E-Service Quality is in the good category, customers are satisfied with the services provided, and the banking image is assessed positively. Statistically, E-Service Quality has a significant effect on customer satisfaction with a direct effect of 67.7%. In addition, E-Service Quality also has a significant effect on banking image by 9.4%. Customer satisfaction has a significant effect on banking image with a contribution of 50.8%. Simultaneously, e-service quality has a strong impact on customer satisfaction, with an influence of 83.2%. This finding underscores the importance of improving e-service quality in building customer satisfaction and banking image.